Produção de bio-óleo a partir da co-pirólise de biomassa de eucalipto e resíduos de poliestireno - Lima, Luisa Coser (2022)
Fossil fuels are widely used to supply the global energy demand, however, they are mainly responsible for the emission of gases that are harmful to the environment. Due to this environmental concern, different sources of renewable energy are sought, among which fuels produced from lignocellulosic biomass stand out. There are several methods of converting biomass into energy and chemical inputs, among which pyrolysis stands out, which is a process in which organic matter is thermally degraded in a non-oxidizing atmosphere. The cooling of the generated vapors leads to the formation of a liquid, called bio-oil, whose quantity and quality depend on the operating conditions and the type of raw material. Due to its composition rich in oxygenated compounds, bio-oil has undesirable characteristics, such as: low calorific value, high acidity and chemical instability. One way to reduce this oxygen content is through the co-pyrolysis technique, in which polymers act as hydrogen donors, resulting in an increase in the calorific value of the fuel. Thus, this work aimed to carry out the copyrolysis of a mixture of eucalyptus and polystyrene residues (PS) and to determine the operational condition in which the highest yield of bio-oil was obtained, evaluating the effects of the final reaction temperature, heating rate and proportion of PS present in the feedstock. The thermal decomposition of the feedstocks was analyzed by thermogravimetric analysis (TGA) and the bio-oils produced were analyzed by gas chromatography coupled to mass spectrometry (GC-MS). The experiments that produced the highest amount of liquid product were carried out at the upper level of the pyrolysis temperature (500 ºC) and the proportion of PS contained in the sample (75%), obtaining bio-oil yields of 70,75% and 70,26%. The heating rate was not a significant parameter in increasing the liquid product yield. Using design of experiment, it was possible to determine the condition in which the maximum yield of bio-oil is obtained, which was 72,15% using the conditions of 70% PS in the feedstock and pyrolysis temperature of 516,45 °C. The composition of the bio-oil produced with only biomass was mostly oxygenated aromatics, while the addition of PS to the feedstock generated bio-oils composed mostly of alkyl aromatics. Decreasing the amount of oxygenated compounds helps to increase the calorific value and stability of the bio-oil.